Global diversity patterns and cross‐taxa convergence in freshwater systems. (22nd November 2012) - Tisseuil, Clement; Cornu, Jean‐François; Beauchard, Olivier; Brosse, Sebastien; Darwall, William; Holland, Robert; Hugueny, Bernard; Tedesco, Pablo A.; Oberdorff, Thierry; Cottenie, Karl
Summary Whereas global patterns and predictors of species diversity are well known for numerous terrestrial taxa, our understanding of freshwater diversity patterns and their predictors is much more limited. Here, we examine spatial concordance in global diversity patterns for five freshwater taxa (i.e. aquatic mammals, aquatic birds, fishes, crayfish and aquatic amphibians) and investigate the environmental factors driving these patterns at the river drainage basin grain. We find that species richness and endemism patterns are significantly correlated among taxa. We also show that cross‐taxon congruence patterns are often induced by common responses of taxa to their contemporary and historical environments (i.e. convergent patterns). Apart from some taxa distinctiveness (i.e. fishes), the 'climate/productivity' hypothesis is found to explain the greatest variance in species richness and endemism patterns, followed by factors related to the 'history/dispersion' and 'area/environmental heterogeneity' hypotheses. As aquatic amphibians display the highest levels of congruency with other taxa, this taxon appears to be a good 'surrogate' candidate for developing global freshwater conservation planning at the river drainage basin grain.